2020
DOI: 10.1016/j.jsxm.2020.04.390
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Alleviates Erectile Dysfunction Associated with Streptozotocin-Induced Type I Diabetes by Ameliorating Endothelial Nitric Oxide Synthase Dysfunction, Inhibiting Oxidative Stress and Fibrosis

Abstract: Background Management of diabetes mellitus induced-erectile dysfunction (DMED) is challenging because of its poor responses to phosphodiesterase type 5 inhibitors. Increasingly important roles of 12-lipoxygenase (12-LOX) have been proven in diabetes mellitus. Aim To investigate 12-LOX activity and therapeutic effect of its inhibitor, baicalein (BE), on DMED. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…47 According to previous studies, apoptosis in the CC of diabetic rats was obviously excessive, and inhibiting apoptosis was an effective way to restore the erectile function of diabetic rats. 19,20 induced diabetic rats and HG-induced nephropathy. 48,49 In this study, BBR treatment reduced the expression of proapoptotic molecules and inhibited excessive apoptosis in the CC of diabetic rats.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…47 According to previous studies, apoptosis in the CC of diabetic rats was obviously excessive, and inhibiting apoptosis was an effective way to restore the erectile function of diabetic rats. 19,20 induced diabetic rats and HG-induced nephropathy. 48,49 In this study, BBR treatment reduced the expression of proapoptotic molecules and inhibited excessive apoptosis in the CC of diabetic rats.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown that when DNA is damaged, increased ERK1/2 can interact with p53 and promote p53 phosphorylation, which may be one of the mechanisms that induces apoptosis 47 . According to previous studies, apoptosis in the CC of diabetic rats was obviously excessive, and inhibiting apoptosis was an effective way to restore the erectile function of diabetic rats 19,20 . Zhu et al.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations